Is European money demand still stable? - Kai Carstensen (Kiel Institute for World Economics (IfW), 2003)
This paper analyzes the question whether money demand in the Euro area has undergone a structural change in recent time when M3 money growth has considerably overshot the reference value set by the European Central Bank (ECB). It is found that conventional specifications of money demand have in fact become unstable while specifications which are augmented with real stock prices and volatility remain stable. Using such an augmented specification, the claim that the excessive M3 growth rates are due to adverse stock market developments is examined. The results indicate that one cannot expect these growth rates to revert in the near future unless one is willing to assume a quick recovery of the European stock markets.
Keywords: 330; Geldnachfrage; Börsenkurs; Volatilität; Schätzung; EU-Staaten